Lack of Systemic Side Effects of Long-Term Inhaled Fluticasone Propionate Use in a Cohort of Asthmatic Children. (January 2013) - Angelini, F.; Corrente, S.; Romiti, M.L.; Moschese, V.; Polito, A.; Chiocchi, M.; Monteferrario, E.; Masala, S.; Chini, L.
Inhaled corticosteroids (ICS) are established as first-line therapy for persistent asthma in children. Fluticasone propionate (FP) has been used because it has equivalent efficacy when used at half-dose of older-generation ICS and has a comparable safety profile. However, concerns persist about the potential risk of adverse effects of long-term FP therapy on childhood growth, bone, adrenal function and immune system. To evaluate the potential adverse effects of FP, we analyzed growth, glucidic metabolism, hypothalamic-pituitary-adrenal axis, bone metabolism, bone mass density and immune system in a cohort of 19 children (average 102±18 months), with asthma who were in treatment with FP (average duration: 14 months, range: 11–17 months). Of these, 11 children homogenous for control of asthma symptoms, and compliance to therapy, were selected for a prospective study during which they were treated with FP250 mg/day for further 6 months (total period of treatment average duration: 22 months, range: 18–23 months). In all children, no alterations of growth, glucidic metabolism, hypothalamic-pituitary-adrenal axis, bone metabolism, bone mass density, immune system nor severe exacerbation of the disease were observed. Our study, showing that FP was able to control the symptoms of asthma and confirming the lack of systemic side effects at the recommended doses, supports its long-term use in children with asthma.